Prevalence of sexually transmitted infections and positive treponemal serology in Solomon Islands guest workers in Australia - Mikaela Seymour; Sean O’Connor; Levi Hou; Sarai Tafa; Sarat Tata; Nicholas Smoll; Stefanie Vaccher; Annie Preston-Thomas; Nishila Moodley (Australian and New Zealand Journal of Public Health)
Objectives: The burden of sexually transmitted infections (STIs) in Pacific guest workers in Australia is currently unknown. Our study determined the prevalence of chlamydia, gonorrhoea, HIV and treponemal infection in a group of predominately Solomon Islands guest workers in Australia in 2023. In addition, we sought to understand the effect of sex, age and type of sexual activity on the risk of STIs in this population group. Methods: Workers under one employer were offered chlamydia and gonorrhoea urine polymerase chain reaction testing, treponemal serology with reflex rapid plasma reagin testing, and HIV testing via antibody/antigen detection. Descriptive analyses identified population characteristics and infection frequencies. Logistic regression was used to estimate the likelihood of diagnosis, reported as odds ratios. Results: The participation rate was 93% (n=391). The median age was 31.9 years (interquartile range: 22.9–40.9) and 86.5% were male. Chlamydia (18.5%) and gonorrhoea (1.8%) were common among guest workers. No cases of HIV were diagnosed. Treponemal-specific reactive tests (48.5%) suggested yaws or syphilis exposure despite being asymptomatic, with 37.1% of these having an rapid plasma reagin titre equal to or exceeding 1:16. Women were 3.71 times more likely to have chlamydia [95% confidence interval (CI) 1.97-6.93]. Conclusion: High rates of chlamydia and positive treponemal serology may reflect high rates of untreated STIs. Implications for Public Health: This unique dataset guides potential screening programs for Pacific guest workers to complement existing education programs.